Preparations for the introduction of a curriculum in technology education into the primary and secondary schools in the CARICOM : report on workshop II - Gift, Edrick...[et al.] ([CARICOM Secretariat] [Georgetown]GY, 2001)
Reports on the preparation of participants of Workshop II, to implement the curriculum guide developed in Workshop 1.